2002
DOI: 10.1074/jbc.m208557200
|View full text |Cite
|
Sign up to set email alerts
|

A Tumor-specific Kinase Activity Regulates the Viral Death Protein Apoptin

Abstract: Apoptin, a chicken anemia virus-encoded protein, is thought to be activated by a general tumor-specific pathway, because it induces apoptosis in a large number of human tumor or transformed cells but not in their normal, healthy counterparts. Here, we show that Apoptin is phosphorylated robustly both in vitro and in vivo in tumor cells but negligibly in normal cells, and we map the site to threonine 108. A gain-of-function point mutation (T108E) conferred upon Apoptin the ability to accumulate in the nucleus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
129
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 25 publications
6
129
1
1
Order By: Relevance
“…26 Similar to DEDD, Apoptin appears to be regulated by translocation to the nucleus, although nuclear localization of Apoptin is not sufficient to induce apoptosis and its phosphorylation appears to be required as well. 14 The finding that Apoptin binds to DEDAF is interesting, because it hints at a possible role of transcription repression in Apoptininduced apoptosis. Recently, we have shown that inhibitors of transcription or translation do not affect Apoptin's activity; however, this does not exclude a function in transcriptional repression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Similar to DEDD, Apoptin appears to be regulated by translocation to the nucleus, although nuclear localization of Apoptin is not sufficient to induce apoptosis and its phosphorylation appears to be required as well. 14 The finding that Apoptin binds to DEDAF is interesting, because it hints at a possible role of transcription repression in Apoptininduced apoptosis. Recently, we have shown that inhibitors of transcription or translation do not affect Apoptin's activity; however, this does not exclude a function in transcriptional repression.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 These data suggest that the tumor-specific activity of Apoptin is not caused by nuclear localization per se. Rather, differential phosphorylation was found to be involved; 14 furthermore, binding to factors that are expressed at higher levels in transformed cells than in normal diploid cells may also play a role.…”
Section: Introductionmentioning
confidence: 97%
“…In cells resistant to apoptin-mediated cell death, the protein has a cytoplasmic localization, whereas in sensitive cells, apoptin is found in the nucleus (Danen-Van Oorschot et al, 2003). Apoptin was described to be specifically phosphorylated in transformed cells by an unknown kinase, which was proposed to be important for the nuclear localization and apoptotic activity of apoptin (Rohn et al, 2002). However, it was also shown that a C-terminally truncated apoptin mutant, in which the phosphorylation site was deleted, was still able to translocate to the nucleus and induce apoptosis (Guelen et al, 2004).…”
mentioning
confidence: 99%
“…In agreement with the interaction data, only those mutants that had the intact interaction site for PI3-K were able to induce apoptosis both in PC-3 and MCF-7 cells (Figure 1c). Interestingly, the mutant Ala-108, which was reported to be noncytotoxic due the substitution of a Thr-phosphorylation site (Rohn et al, 2002), was still able to induce significant apoptosis, as long as its interaction site with the PI3-K remained intact.…”
mentioning
confidence: 99%
See 1 more Smart Citation